Ustekinumab is associated with superior treatment persistence but not with higher remission rates versus vedolizumab in patients with refractory Crohn's disease: results from a multicentre cohort study. (December 2022) - Bacsur, Péter; Matuz, Mária; Resál, Tamás; Miheller, Pál; Szamosi, Tamás; Schäfer, Eszter; Sarlós, Patrícia; Iliás, Ákos; Szántó, Kata; Rutka, Mariann; Bálint, Anita; Milassin, Ágnes; et al.
Background: Treatment with antitumor necrosis factor alpha (anti-TNF-α) is safe and effective as first-line therapy; however, its efficacy is limited due to primary nonresponse (PNR) and secondary loss of response (LOR), resulting in treatment discontinuation in approximately 40%–50% of cases. Vedolizumab (VDZ) and ustekinumab (UST) therapies could be good alternatives in patient with anti-TNF failure; however, no head-to-head randomized comparison of these drugs as second- or third-line treatments has been made. Objectives: This study aimed to assess the treatment persistence and comparative effectiveness of UST and VDZ in patients with refractory Crohn's disease (CD). Design: In this nationwide retrospective study, patients with CD on UST or VDZ maintenance therapy were enrolled. Clinical data at baseline, after induction, and at week 52 were obtained. Methods: Clinical and biochemical activities as well as corticosteroid-free remission (SFR) rates were assessed, while concomitant medications, comorbidities, hospitalizations, and surgeries were recorded during the follow-up to detect any predictors. Results: A total of 161 UST- and 65 VDZ-treated patients completed the follow-up. No significant difference in clinical or biochemical remission rates was observed after induction between the two treatment groups; however, clinical remission rate at week 52 was higher in UST group. UST showed superior drug persistence than VDZ (86.5%, 57.9%, p  < 0.0001). The drug type was predictive of clinical SFR at week 52 [ p  = 0.011, odds ratio (OR) = 2.39 with UST]. Drug failure rates were higher for VDZ than those for UST (PNR rates: 21.54% and 4.97%, respectively, p  < 0.001, OR = 8.267, p  = 0.001). LOR and escalations were more common during UST treatment (61.5% versus 36.9%, p  < 0.001; 64.2% versus 23.1%, p  < 0.001). Hospital and surgical admission rates did not differ significantly. Only one adverse event occurred with VDZ at week 20, which led to drug cessation. Conclusions: VDZ and UST were safe and effective for treating patients with CD in whom anti-TNF therapy failed. UST showed superior drug persistence than VDZ, but dose escalation was more frequent. Biologicals used in lower treatment lines resulted in better drug persistence.